2011
DOI: 10.1093/nar/gkr599
|View full text |Cite
|
Sign up to set email alerts
|

SNVer: a statistical tool for variant calling in analysis of pooled or individual next-generation sequencing data

Abstract: We develop a statistical tool SNVer for calling common and rare variants in analysis of pooled or individual next-generation sequencing (NGS) data. We formulate variant calling as a hypothesis testing problem and employ a binomial–binomial model to test the significance of observed allele frequency against sequencing error. SNVer reports one single overall P-value for evaluating the significance of a candidate locus being a variant based on which multiplicity control can be obtained. This is particularly desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
197
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(200 citation statements)
references
References 35 publications
1
197
0
2
Order By: Relevance
“…First, we conduct SNP calling using both our method EM-SNP and SNVer (parameter setting -bq 20 -a 0 -f 0 -p 1 -t 0) [11], a program that has been shown to outperform several other programs for SNP calling including CRISP, SAMtools, and GATK. Unlike many previous programs calling variants as SNPs or not, SNVer ranks variants according to their potential of being true SNPs using the p-value defined in the program.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we conduct SNP calling using both our method EM-SNP and SNVer (parameter setting -bq 20 -a 0 -f 0 -p 1 -t 0) [11], a program that has been shown to outperform several other programs for SNP calling including CRISP, SAMtools, and GATK. Unlike many previous programs calling variants as SNPs or not, SNVer ranks variants according to their potential of being true SNPs using the p-value defined in the program.…”
Section: Resultsmentioning
confidence: 99%
“…Altmann et al [13] improved the computational speed of CRISP and identified SNPs as the variants with different minor allele frequencies across at least two pools. Wei et al [11] developed a statistical tool, called SNVer, for variant identification. For each pool, SNVer first defined a p-value by testing the hypothesis that the minor allele frequency is above a given threshold and then combined the p-values for individual pools to give an overall p-value using Simes methods as in [12].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for longer reads, when the quality scores for the later positions are worse than those for the earlier positions. The minimum achievable detection frequency for a minor allele has been reported in the literature to be between 3% and 0.1% [22][23][24][25][26][27] and as our data are derived from FFPE-treated DNA samples it is not surprising that our minimum allele frequency cutoff is toward the upper end of this range.…”
Section: Discussionmentioning
confidence: 50%
“…Single reads were mapped against the genome of R. sphaeroides WS8N (45) using bowtie2. The .SAM file was converted to .bam and visualized with Artemis and SNVER (46)(47)(48)(49)(50) to identify the differences between the genome sequence and the mapped reads. The changes that were consistently present in all the reads at a particular position were confirmed by PCR followed by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%